Escapism-Based Motivation Affected the Psychological Performances of High-Risk Internet Gaming Disorder Individuals - Wang, Shuai; Li, Jialing; Wang, Siyu; Mi, Can; Wang, Wei; Xu, Zhengjia; Xiong, Wenjing; Tang, Longxing; Li, Yanzhang (Frontiers in Psychiatry, 2022)
Background: Escapism-based motivation (EBM) is considered as one of the diagnostic criteria for internet gaming disorder (IGD). However, how EBM affects the high risk of IGD (HIGD) population remains unclear. Methods: An initial number of 789 college students participated in the general, internet gaming behavior, and motivation surveys. After multiple evaluations, 57 individuals were identified as HIGD (25 with EBM, H-EBM; 32 with non-EBM, H-nEBM). In addition, 51 no-gaming individuals were included as the control group (CONTR). The cohorts completed the psychological assessments and eye-tracking tests, and analyses of group differences, correlations, and influencing factors of the indicators were performed. Results: The Barratt impulsiveness score of H-nEBM and H-EBM was significantly higher than that of CONTR (MD = 3.605, P = 0.017; MD = 3.744, P = 0.022). In addition, emotional intelligence self-emotion management ability was significantly lower in the H-EBM than in CONTR (MD = –2.038, P = 0.004). Correct rates and reaction times in the anti-saccade task differed significantly between the three groups (F = 3.525, P = 0.033; F = 4.459, P = 0.014). However, no differences were found in the comparison of the digital span test (DST), trail making test (TMT), animal verbal fluency test, Stroop test, and mental rotation test results. The anti-saccade test indicators were positively correlated with the DST results but negatively correlated with the Stroop test results (P < 0.05). Correct rates in the mental rotation test were negatively correlated with the TMT results but positively correlated with the DST results (P < 0.05). The participants with high Stroop test scores and no lover experience and who were raised by their grandparents were likely to develop EBM to engage in high risk of internet gaming disorder (P < 0.05). Conclusion: EBM has a significantly negative effect on impulsivity, self-emotion management ability, and response inhibition in the HIGD participants.